2017
DOI: 10.3389/fpsyg.2017.02252
|View full text |Cite
|
Sign up to set email alerts
|

Child/Adolescent’s ADHD and Parenting Stress: The Mediating Role of Family Impact and Conduct Problems

Abstract: Objective: The demands of parenting are usually associated with some stress, and elevated levels of stress may affect the parent–child relationships and parenting practices. This is especially the case of families where children have special needs conditions or disorders, like Attention Deficit Hyperactivity Disorder (ADHD).Method: This study examined parenting stress among mothers of children and adolescents with ADHD. The sample comprised 126 mothers of girls (36; 29%) and boys (90; 71%) aged 6–17 years old.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 82 publications
(124 reference statements)
4
47
0
1
Order By: Relevance
“…Muñoz-Silva et al [26] found (a) high level of parenting stress was related to the severity of symptoms of children with ADHD and behavior/ emotional problems, greater interparental conflict/ disagreement; and (b) contextual factors predict parenting stress over and above the children problems and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Muñoz-Silva et al [26] found (a) high level of parenting stress was related to the severity of symptoms of children with ADHD and behavior/ emotional problems, greater interparental conflict/ disagreement; and (b) contextual factors predict parenting stress over and above the children problems and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…The stress occurs both in the parent domain (restrictions, feelings of social alienation, conflict with the partner, feelings of guilt and incompetence) and in the domain of the relationship with their children (Wiener, Biondic, Grimbos & Herbert, 2016). Furthermore, the children's problems, in addition to having a negative impact on the family's social life, have been shown to mediate in the association between child and adolescent ADHD and parenting stress (Muñoz-Silva, Lago-Urbano, Sanchez-Garcia & Carmona-M arquez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that ADHD comorbid problems were significant influencing factors to parenting stress. 33 Comorbid problems should be included in our future studies since we did not collect the information of this aspect in the present study. In the ASD group, caregivers experienced a higher level of stress when their children exhibited more self-harm or stereotyped behaviours.…”
Section: Discussionmentioning
confidence: 99%